Effectiveness of phenomenon-based peer assessment learning model on college students’ entrepreneurship skills and critical thinking - Yue, Ye; Sitthiworachart, Jirarat; Ratanaolarn, Thanin (Edelweiss Applied Science and Technology, 2026)
Entrepreneurial skills and critical thinking skills have become indispensable for adapting to market demands and securing suitable future career positions for today’s college students. This study integrated Phenomenon-Based Learning, peer assessment, and generative AI into the PhBLPA model to examine its effectiveness in enhancing students’ entrepreneurial skills and critical thinking in entrepreneurship education. A two-group posttest-only experimental design was employed, involving two groups selected through cluster sampling, with 40 students per group, totaling 80 students. The experiment spanned eight weeks as part of an entrepreneurship course. Entrepreneurial skills were assessed through students’ entrepreneurial business project plans, while critical thinking was measured using a five-point Likert scale questionnaire. The data obtained were analyzed using MANOVA, revealing significant differences between groups. The results supported Research Hypothesis 1 (RH1): students who studied the PhBLPA model demonstrated higher entrepreneurial skills than those who studied with traditional learning methods (P < .001). Similarly, Research Hypothesis 2 (RH2): students who studied the PhBLPA model exhibited higher critical thinking skills than those who studied with traditional methods (P < .001). Overall, the findings suggest that the PhBLPA model is more effective than traditional methods for cultivating 21st-century entrepreneurial skills and critical thinking among university students.